Regulation of endo‐lysosomal pathway and autophagic flux by broad‐spectrum antipathogen inhibitor ABMA. (21st January 2020) - Wu, Yu; Boulogne, Claire; Carle, Stefan; Podinovskaia, Maria; Barth, Holger; Spang, Anne; Cintrat, Jean‐Christophe; Gillet, Daniel; Barbier, Julien
Abstract : The endo‐lysosome system is involved in endocytosis, protein sorting, and degradation as well as autophagy. Numerous toxins and pathogens exploit this system to enter host cells and exert their deleterious effects. Modulation of host endo‐lysosome pathway may restrict multiple toxins intoxication as well as pathogen infection. ABMA, selected from a high‐throughput screening against the cytotoxicity of ricin toxin, exhibits a broad‐spectrum antitoxin and antipathogen activity. Here, we show that ABMA selectively retains endocytosed protein and toxin to late endosomes and thus delaying their intracellular trafficking. It also impairs the autophagic flux by excessive fusion of late endosomes and autophagosomes. Its exclusive action on late endosomes and corresponding consequences on the endo‐lysosomal pathway and autophagic flux are distinct from known inhibitors such as bafilomycin A1, EGA, or chloroquine. Hence, besides being a broad‐spectrum inhibitor of endocytosed toxins and pathogens, ABMA may serve as a molecular tool to dissect endo‐lysosome system‐related cellular physiology and mechanisms of pathogenesis. Abstract : ABMA, selected from a high‐throughput screening against the cytotoxicity of ricin toxin, exhibits a broad‐spectrum anti‐toxin and anti‐pathogen activity. We reveal that ABMA selectively retains endocytosed protein and toxin to late endosomes, and thus delaying their intracellular trafficking. It also impairs the autophagic flux by excessive fusion of late endosomes and autophagosomes. ABMA may serve as a molecular tool to dissect endo‐lysosome system‐related cellular physiology and mechanisms of pathogenesis.